Immunoexpression of interleukin 17, transforming growth factor β1, and forkhead box P3 in periapical granulomas, radicular cysts, and residual radicular cysts - Andrade, Ana Luiza Dias Leite de (2013)
INTRODUCTION: Different cell types and cytokines have been identified as contributors to the formation of periapical lesions. In this perspective, this study aimed to evaluate the immunoexpression of interleukin (IL)-17, transforming growth factor (TGF)-β1, and the forkhead box P3 (FoxP3) in periapical lesions, correlating them with the type of lesion, the intensity of the inflammatory infiltrate, and the thickness of the cystic epithelial lining. METHODS: Twenty periapical granulomas (PGs), 20 radicular cysts (RCs), and 20 residual radicular cysts (RRCs) were submitted to immunohistochemical analysis using anti-IL-17, anti-TGF-β1, and anti-FoxP3 antibodies. RESULTS: In comparison with PGs and RCs, RRCs exhibited a lower immunoexpression of IL-17 and TGF-β1 (P = .021 and P < .001, respectively). The number of FoxP3+ cells increased in this order: RRCs, RCs, and PGs (P < .001). In comparison with lesions with inflammatory infiltrates grades I and II, lesions with inflammatory infiltrate grade III exhibited a higher number of FoxP3+ cells (P = .002). Similarly, in comparison with lesions with inflammatory infiltrates grades II and III, lesions with inflammatory infiltrate grade I showed a tendency for a lower expression of IL-17 and TGF-β1 (P = .085 and P = .051, respectively). For all groups, there was a positive correlation between the immunoexpressions of IL-17 and TGF-β1 (P < .05). Positive correlations between the number of FoxP3+ cells and the immunoexpressions of IL-17 and TGF-β1 (P < .05) were found only in PGs. CONCLUSIONS: Th17 and Treg cells seem to interact at the site of injury, suggesting the involvement of proinflammatory and immunoregulatory cytokines in the pathogenesis of periapical lesions.